The role of national service in combating social extremism in the United Arab Emirates (UAE) - Al-Ameeri, Khalled Ali Mohammed; Alomosh, Ahmad Falah (Al-Adab Journal, 2020)
The issue of extremism has become a prominent phenomenon in society in recent decades and has taken dangerous religious, political and societal dimensions and has had dire consequences, bad results and negative repercussions on the nation and humanity in particular. This phenomenon has led to the emergence of a set of unacceptable behaviors such as violence, intolerance and terrorism. Then came the National Service Law, which had social, cultural and educational effects on young people. The national service contributes to controlling the proper behavior of most young people through military training, as their joining the military sectors helps to produce a generation of young people who are committed to its work, behaviors, and obedience to its superiors, and instills in them confidence, patriotism, and respect for time, while acquiring skills that prepare young people for self-reliance and ability on determining their future options based on the experience they had during the training period. And all of this is reflected in society, as in the goodness and strength of the youth, society is stable and stable. National service plays a crucial role in cultivating youth personalities, promoting good morals and behaviors among their ranks, fostering patriotism and loyalty to it, and loyalty to its wise leadership, a sustainable belief across successive generations.